2015
DOI: 10.1007/s12207-015-9219-1
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Results: Assessment of Response Bias Through Select Self-Report Measures in Psychological Injury Evaluations

Abstract: Forensic psychological injury evaluations require extensive consideration of malingering and response bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Iverson & Binder, 2000) or examining over-endorsement of physical or psychological symptoms on self-report tests (Merten, Merckelbach, Giger, & Stevens, 2016). Such tests are called Symptom Validity Tests and have shown to be useful in forensic settings (see Bianchini, Mathias, & Greve, 2001;Sleep, Petty, & Wygant, 2015), but less so in medical settings (Rogers, Sewell, & Salekin, 1994;Schoenberg, Dorr, & Morgan, 2003).…”
mentioning
confidence: 99%
“…Iverson & Binder, 2000) or examining over-endorsement of physical or psychological symptoms on self-report tests (Merten, Merckelbach, Giger, & Stevens, 2016). Such tests are called Symptom Validity Tests and have shown to be useful in forensic settings (see Bianchini, Mathias, & Greve, 2001;Sleep, Petty, & Wygant, 2015), but less so in medical settings (Rogers, Sewell, & Salekin, 1994;Schoenberg, Dorr, & Morgan, 2003).…”
mentioning
confidence: 99%
“…The most frequently used methods for the detection of malingering involve examining intentional underperformance on simple memory tasks (e.g., Iverson & Binder, 2000) or examining over-endorsement of physical or psychological symptoms on self-report tests (Merten, Merckelbach, Giger, & Stevens, 2016). Such tests are called Symptom Validity Tests (SVTs) and have shown to be useful in forensic settings which involve malingering (see Sleep, Petty, & Wygant, 2015;Bianchini, Mathias, & Greve, 2001), but are less often applied in clinical (diagnostic) settings (Schoenberg, Dorr, & Morgan, 2003;Roger, Sewell, & Salekin, 1994).…”
Section: The Verifiability Approach To Detect Malingering Of Physicalmentioning
confidence: 99%
“…As for some of the research in support of the MMPI-2-RF in the forensic disability and related context, Sleep et al (2015) noted that Wygant, Anderson, Sellbom, Rapier, Allgeier, and Granacher (2011) found the Fs and FBS-r scales were Bgood at identifying noncredible neurocognitive and somatic symptoms^in litigation-related compensation-seeking examinees undergoing disability evaluations who were classified at malingering levels using the MND and MPRD criteria.…”
Section: Reviewmentioning
confidence: 99%
“…Young (2014a) reviewed the literature related to these tests in the forensic disability and related context, and found that the research on the MMPI-2-RF, in particular, was burgeoning (even by workers other than the test founders) and supported its use in these assessments. Sleep, Petty and Wygant (2015) described that one MMPI-2 over-reporting indicator is the Infrequency (F) scale. It includes rare psychopathological symptoms endorsed by <10 % of the original MMPI normative sample.…”
Section: Testing Introductionmentioning
confidence: 99%
See 1 more Smart Citation